Long‐term stability in core habitat of an endangered population of bottlenose dolphins (Tursiops truncatus): Implications for spatial management. Issue 3 (15th September 2020) - Bennington, Steph; Rayment, Will; Currey, Rohan; Oldridge, Lucy; Henderson, Shaun; Guerra, Marta; Brough, Tom; Johnston, David; Corne, Chloe; Johnson, David; Slooten, Liz; Dawson, Steve
Abstract: A small population of approximately 68 bottlenose dolphins, Tursiops truncatus, resident in Doubtful Sound, New Zealand, is subject to physiologically challenging conditions, and is exposed to anthropogenic pressure from tourism. A voluntary Code of Management incorporating dolphin protection zones (DPZs), in which tour boat access is limited, was established in 2008. Kernel density estimation (KDE) was used to quantify dolphin habitat use over a 13‐year period in order to describe seasonal variation in habitat use and consistency of habitat use over a decadal period, and to provide quantitative estimates of the extent of overlap between DPZs and core areas (50% volume contour) of habitat use. Habitat use varied seasonally, with the inner fjord area used more frequently in warmer months, and with a shift in use to the outer fjord in colder months. Patterns in habitat use were highly consistent over the 13‐year duration of the study. The spatial overlap between the area of core dolphin habitat and DPZs was low (<18%) overall, and some DPZs were rarely used during colder periods. Consistency in habitat use through time vindicates spatial management, but low overlap between core habitat and current DPZs suggests that an expansion of the DPZ areas would confer greater protection.